The Structure and Properties of Yttrium-Stabilized Zirconium Dioxide Ceramics Treated by Electron Beam - Tolkachev O. S. Oleg Sergeevich; Ivanov Yu. F. Yuriy Fedorovich; Petrikova E.; Petyukevich M. S. Mariya Stanislavovna; Panina A. A. Aleksandra Anatolievna (Physicochemical Properties of Materials and Current Processing Technologies, 2016)
Title screen